2006
DOI: 10.1021/ic060050q
|View full text |Cite
|
Sign up to set email alerts
|

Heterobimetallic Activation of Dioxygen:  Characterization and Reactivity of Novel Cu(I)−Ge(II) Complexes

Abstract: Reaction of the known germylene Ge[N(SiMe 3 ) 2 ] 2 and a new heterocyclic variant Ge [(NMes) 2 (CH) 2 ] with [L Me2 Cu] 2 (L Me2 = the β -diketiminate derived from 2-(2,6-dimethylphenyl) amino-4-(2,6-dimethylphenyl)imino-2-pentene) yielded novel Cu(I)-Ge(II) complexes L Me2 Cu-Ge [(NMes) 2 (CH) 2 ] (1a) and L Me2 Cu-Ge[N(SiMe 3 ) 2 ] 2 (1b), which were characterized by spectroscopy and X-ray crystallography. The lability of the Cu(I)-Ge(II) bond in 1a and b was probed by studies of their reactivity with benz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 41 publications
7
81
1
Order By: Relevance
“…The benzo-anellated bis(NHGe)-Mo(CO) 4 chelate complex 4 [23] behaves similarly to 2b, with displacements for Ge of 13.5 pm and for Mo of 65 pm, whereas in a sterically even more challenging but non-anellated (dimesityl-NHGe)Cu I complex there are no marked deviations from planarity (Ge: 0.8 pm; Cu: 2.8 pm). [31] To shed light on the background of the folding observed for the anellated NHGe carbonyl molybdenum(0) and nickel(0) complexes (Figure 3), we calculated the structure of 2a in the gas phase, along with the structures of [Ge{(NtBu) 2 . Compound 2a is planar in the solid state [15c] with both neopentyl groups on the same side, but the 0.22 kcal mol -1 required to achieve planarity can easily be provided by packing effects.…”
Section: Pes and Quantum Chemical Calculationsmentioning
confidence: 99%
“…The benzo-anellated bis(NHGe)-Mo(CO) 4 chelate complex 4 [23] behaves similarly to 2b, with displacements for Ge of 13.5 pm and for Mo of 65 pm, whereas in a sterically even more challenging but non-anellated (dimesityl-NHGe)Cu I complex there are no marked deviations from planarity (Ge: 0.8 pm; Cu: 2.8 pm). [31] To shed light on the background of the folding observed for the anellated NHGe carbonyl molybdenum(0) and nickel(0) complexes (Figure 3), we calculated the structure of 2a in the gas phase, along with the structures of [Ge{(NtBu) 2 . Compound 2a is planar in the solid state [15c] with both neopentyl groups on the same side, but the 0.22 kcal mol -1 required to achieve planarity can easily be provided by packing effects.…”
Section: Pes and Quantum Chemical Calculationsmentioning
confidence: 99%
“…Keywords: copper · density functional calculations · dioxygen · enzyme models · hydroxylation · oxidation Whereas coupled dinuclear copper systems have been the subject of a large number of theoretical and experimental studies, [28][29][30] investigations of the oxidative processes induced by mononuclear copper-O 2 adducts are less common. The main reason is that model compounds usually undergo fast dimerization or exhibit slow reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…The novel Cu(I)-Ge(II) containing compound Cu(BDI Ar ) [Ge(N{SiMe 3 } 2 ) 2 ] (Ar = 2,6-Me 2 C 6 H 3 , 87) was reported in 2006, in which the copper centre was supported by a bidentate BDI-ligand [78]. It was shown that this bond can be readily cleaved by donor ligands such as PPh 3 or an NHC with liberation of the free germylene, whereas reaction with O 2 insterted into the Cu Ge bond to afford the Cu(II)-Ge(IV) species, Cu(BDI Ar )( -O) 2 [Ge(N{SiMe 3 } 2 ) 2 ] (88, Eq.…”
Section: Germaniummentioning
confidence: 99%